Exploring school resilience in the context of globalizing digital change: the impact on teacher management - Abdallah, Asma Khaleel; Shagivaleeva, Guzalia; Kolomoets, Elena (Institute of Advanced Engineering and Science, 2025)
Administrators in educational institutions will need to implement smart and well-designed changes in teacher management to mitigate the negative effects. Using teacher resilience as an example, the study seeks to assess the level of resilience in schools and analyze its effects on teacher management. The study includes 197 teachers from 31 Russian schools in Kazan, Elabuga, Moscow, and Yekaterinburg, and 100 foreign teachers working in United Arab Emirates. The research design was descriptive transactional and based on a questionnaire. The study yielded the following findings: i) 89.4% of teachers have a high level of stress, 94.2% have a high level of worry, 92.3% have a high level of anxiety, 33.8% have a low level of resilience, and 95.7% were in a difficult emotional state and ii) the inquiry-based stress reduction (IBSR) practice had a positive effect on increasing teacher resilience. This indicated that implementing such changes in teacher management might be successful in boosting teacher resilience, which would affect school resilience generally. Educational researchers have confirmed the effectiveness of the IBSR tool in boosting teacher resiliency, and the results of this study can aid school administrators in developing new management models utilizing this tool.